2011
DOI: 10.1007/s10238-010-0130-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed genes in human rectal carcinoma using suppression subtractive hybridization

Abstract: The existence and treatment of rectal cancer are important for the function of defecation and the quality of life. However, the precise mechanisms of rectal carcinogenesis remain unclear. To screen the overexpressed gene in rectal carcinoma, we performed suppressive subtractive hybridization (SSH) on rectal carcinoma cells and the corresponding normal rectal cells. A total of 64 recombinant clones were subjected to DNA sequencing analysis, and 9 known genes were found to overexpressed in the tumors compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…For instance it has been reported that PCA-1/ALKBH3 was specifically expressed and contributed to cell survival and invasion in human prostate cancer (10,24) and in human non-small cell lung cancer (11). In gastrointestinal tumor, it has been reported that in rectal cancer tumor tissues overexpressed PCA-1/ALKBH3 compared with normal rectal tissues, although the function and the role of PCA-1/ALKBH3 have not been addressed (38). It was also reported that PCA-1/ALKBH3 was one of the candidate gene associated with the risk of papillary thyroid cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…For instance it has been reported that PCA-1/ALKBH3 was specifically expressed and contributed to cell survival and invasion in human prostate cancer (10,24) and in human non-small cell lung cancer (11). In gastrointestinal tumor, it has been reported that in rectal cancer tumor tissues overexpressed PCA-1/ALKBH3 compared with normal rectal tissues, although the function and the role of PCA-1/ALKBH3 have not been addressed (38). It was also reported that PCA-1/ALKBH3 was one of the candidate gene associated with the risk of papillary thyroid cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…This gene maps to 14q32.33, a chromosomal region of frequently observed cytogenetic alterations in B-cell malignancies (52). It was also reported that NUDT14 is overexpressed in human rectal carcinoma (40). RGS20 belongs to a family of proteins with conserved GTPase-activating domain of approximately 120 amino acid residues.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently validated the microarray results by qRT-PCR of several genes, ADCY7, ARGHDIB, BAMBI, FOXG1, FSCN1, FUCA1, GFPT2, ITPR3, ITGA4, LSP1, NCAM1, NUDT14, RGS20, RHOF, and RIAM, that have already been implicated in cell migration, adhesion, or angiogenesis (28,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The results from qRT-PCR analysis (Fig.…”
Section: Differential Gene Expression Analysis Of Pr9692shmock and Prmentioning
confidence: 99%
“…It was also reported that SCL interacted with SPS1 [17]. Further, the fact that SPS1 is overexpressed in rectal carcinoma cells suggested that SPS1 levels are related to cancer development [18]. In addition to growth retardation and induction of the cellular defense system, SPS1 deficiency also led to the accumulation of reactive oxygen species (ROS) in Drosophila both in vivo and in vitro [14, 19].…”
Section: Introductionmentioning
confidence: 99%